Multiplex crack smoking and sexual networks: Associations between network members’ incarceration and HIV risks among high-risk MSM - Fujimoto, Kayo (J Behav Med, 2016)
OBJECTIVES: This study examined HIV risks in the multiplex crack-smoking and sexual networks of incarcerated drug-using men who have sex with men (MSM) and their associates. We estimated the associations between the network members’ incarceration, self-reported HIV infection, and trading sex for money. METHODS: Our analytic sample consisted of 508 crack-smoking or sexual partnerships of 273 high-risk MSM. Network members were specified by (1) crack smoking and sexual behavior or (2) crack smoking only. RESULTS: Longer incarceration of the crack-smoking and sexual network members was associated with self-reported HIV infection (AOR = 1.61, p < 0.05), which extended up to one’s partners’ partners’ partners (AOR = 1.63, p < 0.05). Similar results were found for trading sex (AOR = 2.77, p < 0.05). CONCLUSIONS: The findings of the study call for the development of a system-level HIV intervention among former incarcerated MSM and their associates.